Troponin T: how high is high? Relationship and differences between serum cardiac markers according to level of creatine kinase and type of myocardial infarction. Issue 948 (5th October 2004) - Williams, S G; Silas, J H; Joseph, F; Jackson, M; Rittoo, D; Currie, P
Abstract : Cardiac troponins have emerged over recent years as the "gold standard" serum biochemical marker for the diagnosis and management for patients with acute myocardial infarction (MI). The relationship between old (creatine kinase; CK) and new (troponin T; TT) markers of myocardial injury were examined in this study of 392 consecutive patients admitted to a district hospital with a diagnosis of an acute MI. Significant correlation of serum TT and peak CK levels were seen ( R = 0.58, p<0.0001) in all types of MI. A significant relationship was also seen according to type of MI (Q wave or non-Q wave MI) or peak CK level. The regression equation (TT (μg/l) = 0.0027 (peak CK) + 1.1160 (IU/l)) may be used by clinicians to estimate TT release from a known peak CK result and thus provide some guidance on equivalence between the two tests. Our findings provide physicians with a benchmark reference range between the two cardiac markers, according to level of peak CK.